Self-Disclosure and Self-Confidence with TikTok Usage Intentions in Gen Z - Rinanti Resmadewi; Imtihanatul Ma’isyatuts Tsalitsah; Agus Poerwanto (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Generation Z is the current generation who are accustomed to using gadgets and social media. While Tik Tok is one of the social media that is favored by teenagers. With Tik Tok, teenagers can show themselves to the public with a variety of expressions and creativity. The purpose of this study was to see whether there is a relationship between self-disclosure and self-confidence with the intention to use social media Tik Tok in generation Z. The population in this study is generation Z in the city of Surabaya who actively use Tik Tok. The sampling technique used purposive sampling, with a sample of 91 respondents. Based on the results of the multiple regression test, it shows that there is a joint relationship between self-disclosure and confidence in the intention to use TikTok in generation Z in the city of Surabaya, with a significance of 0.002 <0.05. However, if each variable is tested, the result is that the confidence variable obtains a value of p = 0.062 (p > 0.05), which means that there is no relationship between self-confidence and the intention to use TikTok.